Peningkatan Pelayanan Ekowisata Badher Bank Melalui Pendampingan Manajemen Kelompok - Muammar Kadhafi; Ledhyane Ika Harlyan; Tri Djoko Lelono; Sukandar Sukandar; Sunardi Sunardi; Abu Bakar Sambah; Eko Sulkhani Yulianto; Darmawan Ockto Sutjipto; Yasinta Rahmaningtyas; Tantowi Joan Fauzi (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Tawangrejo fishers located in Binangun, Blitar are a group of fishers who conducted destructed fishing. Once fish population decreased, they believed that they must recover the fish population in the Brantas river, especially for a ray-finned fish, Puntius bramoides (Valenciennes, 1842) that live endemic, by forming Community based surveillance named POKMASWAS Fajar Bengawan. The POKMASWAS actively monitor and prohibit destructive fishing, also initiate ecotourism called Badher Bank such as river tracking, fish feeding and fishing. However, Badher Bank still has some constraints related to service management and infrastructure availability. Therefore, the aim of these activities was to increase the service of Badher Bank ecotourism by assisting the group management and building a rest facility for tourists. The results of these activities were the workshop and capacity building for POKMASWAS and the provision of a gazebo. Now, Badher Bank has been well managed with improved management skills and excellent ecotourism services.